2019
DOI: 10.3389/fmicb.2019.02865
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Flagellar, Fimbriae, and Pili Proteins in Carbapenem-Resistant Klebsiella pneumoniae (NDM-4) Clinical Isolates: A Novel Linkage to Drug Resistance

Abstract: The emergence and spread of carbapenem-resistant Klebsiella pneumoniae infections have worsened the current situation worldwide, in which totally drug-resistant strains (bad bugs) are becoming increasingly prominent. Bacterial biofilms enable bacteria to tolerate higher doses of antibiotics and other stresses, which may lead to the drug resistance. In the present study, we performed proteomics on the carbapenemresistant NDM-4-producing K. pneumoniae clinical isolate under meropenem stress. Liquid chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“… 31 , 32 The latter is an important bacterial defense system. 33 Interestingly, K. pneumoniae , a common biofilm-forming bacterium that expresses flagella 34 but circumvents IgA coating in our dataset. In contrast, E. coli , also flagellum-bearing, is heavily coated with IgA.…”
Section: Discussionmentioning
confidence: 93%
“… 31 , 32 The latter is an important bacterial defense system. 33 Interestingly, K. pneumoniae , a common biofilm-forming bacterium that expresses flagella 34 but circumvents IgA coating in our dataset. In contrast, E. coli , also flagellum-bearing, is heavily coated with IgA.…”
Section: Discussionmentioning
confidence: 93%
“…To search the global protein patterns of different KPN clinical isolates, a total of 15 KPN strains, including three sensitive (SEN), three amikacin-resistant (AMI), three cotrimoxazole-resistant (CTX), and three amikacin/cotrimoxazole both-drug-resistant (ACB) KPN isolates derived from 12 different patients ( Table 1 ) in our hospital, as well as three ATCC type strains, were collected and subjected to LC-MS/MS in single runs by a quadrupole Orbitarp instrument after trypsin digestion for label-free proteomics analysis ( Figure 1A ). As a result, a deep coverage of 2,266 proteins were successfully identified and quantified in total ( Figure 1B and Supplementary Table 1 ), expanding the experimental coverage of the 5,126 predicted bacterial gene products (in KPN database from UniprotKB, strain ATCC 700721) from 23% (1,156) ( Sharma et al, 2019 ), 32% (1,654) ( Keasey et al, 2019 ) to 44%, providing an extended characterization of KPN proteome. The dynamic ranges of protein quantification values in this study spanned over six orders of magnitude ( Supplementary Figure 1A ), with the most abundant proteins being rpsU, HupA, tufa, etc.…”
Section: Resultsmentioning
confidence: 99%
“…By re-analyzing the data reported previously, we found the deficiencies of resistant KPN in central metabolic pathways was a generally existent phenomenon. Briefly, the metabolic process, cellular process and response to stimulus were downregulated in ESBL-producing KPN ( Wang Y. et al, 2020 ), and the Carbohydrate metabolic process, Generation of precursor metabolites and energy, Cellular amino acid metabolic process, Lipid metabolic process, Catabolic process, were all downregulated in carbapenem-resistant KPN ( Sharma et al, 2019 ). These findings showed that restraint of TCA cycle pathway could be a widely used strategy of KPN to gain antibiotic resistance, showing a non-antibiotic based therapeutic method against antibiotic-resistant infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, upon entry and colonisation in the airway, bacteria have the ability to acquire phenotypic changes displaying a shift from a free-living planktonic state to complex sessile community of microorganisms encapsulated in an extracellular matrix (biofilm) ( Figure 1 ) [ 53 ]. This occurs through the change in expression of virulence factors, such as type 3 secretion systems [ 54 , 55 ] and flagellum [ 56 , 57 ], both of which are downregulated, along with the secretion of exoproducts to reduce host bacterial killing [ 58 ] overall, facilitating and promoting the establishment of chronic pulmonary infections [ 16 , 59 , 60 ]. Chronic airway infections are a major problem faced by pwCF and are difficult to eradicate, often requiring long-term suppression with inhaled antibiotics and, consequently, increasing the risk of developing further antimicrobial resistance, trapping these patients in a vicious cycle of infection and inflammation.…”
Section: Microbiome In Cfmentioning
confidence: 99%